Ambulatory Management Strategies for Obstructive Sleep Apnea - Chai-Coetzer, Ching Li; Aiyappan, Vinod; Antic, Nick A. (Seminars in Respiratory and Critical Care Medicine, 2014)
The prevalence of obstructive sleep apnea (OSA) has been steadily rising over recent decades and patient access to laboratory-based sleep services and specialist consultations have become increasingly limited, resulting in potential delays in treatment. As a result, there has been growing interest in the use of non-sleep laboratory methods for diagnosing and managing OSA, including the use of screening questionnaires, portable sleep monitoring devices, and home autotitrating continuous positive airway pressure. There is also evidence in support of a role for alternative health care professionals, such as sleep-trained nurses and primary care physicians in the diagnosis and treatment of OSA. In this review, we compare the different types of home monitoring devices, discuss the limitations of portable monitoring compared with full laboratory polysomnography, and summarize the results from published comparative effectiveness studies which have evaluated ambulatory models of care for the management of OSA. We also consider how future models of care that may be needed to deal with the burden of disease will evolve and some of the issues that prevent the translation of such models of care in many countries.
Keywords: obstructive sleep apnea; polysomnography; ambulatory model; portable monitoring; home diagnosis; screening questionnaires; autotitrating continuous positive airway pressure